Parasite diversity and ecology in a model species, the guppy (Poecilia reticulata) in Trinidad - Ryan S. Mohammed; Stanley D. King; Paul Bentzen; David Marcogliese; Cock van Oosterhout; Jackie Lighten (Royal Society Open Science, 2020)
The guppy (Poecilia reticulata) is a model species in ecology and evolution. Many studies have examined effects of predators on guppy behaviour, reproduction, survival strategies, feeding and other life-history traits, but few have studied variation in their parasite diversity. We surveyed parasites of 18 Trinidadian populations of guppy, to provide insight on the geographical mosaic of parasite variability, which may act as a source of natural selection acting on guppies. We found 21 parasite species, including five new records for Trinidad. Spatial variation in parasite diversity was significantly higher than that of piscine predators, and significant variation in parasite richness among individuals and populations was correlated with: (i) host size, (ii) snail species richness, and (iii) the distance between populations. Differences in parasite species richness are likely to play an important, yet underestimated role in the biology of this model species of vertebrate ecology and evolution.